Friction Stir Welding pada Paduan Aluminium 6061 dan HDPE menggunakan Mesin Frais - Basuki, Widodo Widjaja; Ginting, Eliata Dumar; Hudaya, Hoo Bram Natanael; Sutanto, Hadi; De Fretes, Anthon; Widiarto, Sandra Octaviani B. (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2024)
Friction stir welding (FSW) is a solid-state welding method that is very simple, cheap, and in principle only requires equipment to rotate the tool and move the workpiece translationally. In this research, it was demonstrated that the FSW process of aluminum alloy 6061 and high-density polyethylene (HDPE) polymer is possible using a vertical milling machine, however, modifications need to be made to make it possible to regulate the pressure applied by the milling machine through the tool shoulder to the surface of the workpiece. Apart from that, it was also known that for each material undergoing the FSW process, it is necessary to determine the right parameter set which is a combination of rotational speed and tool feed speed to obtain optimal welding results. Too high a tool rotation speed can cause high lifting forces which can produce large porosity in the workpiece. For the HDPE FSW process, too high a tool rotation speed, which is not balanced with the increase in feed speed will provide excessive heat, causing depressions on the surface of the nugget zone.